It happened here first - Gifford, Clive (London Kingfisher, 2009)
From the quirky and the humorous to the truly ground-breaking. This is a unique, irresistible pictorial miscellany celebrating thousands of years of human achievement. It reveals who won the first-ever Air Guitar world Championships, which building was the world's first skyscraper, and where the Wright brothers first flew
Reference Material
EYE students
Keywords: Children's nonfiction; Curiosities and wonders